Low-cycle fatigue behavior of austenitic stainless steels with gradient structured surface layer. (May 2020) - Ho, H.S.; Zhou, W.L.; Li, Y.; Liu, K.K.; Zhang, E.
Highlights: LCF behaviors of GSed 316L steels produced by shot peening is investigated. Hysteresis energy-based model is used for fatigue analyses of GSed 316L steels. Fatigue damage characteristics of GSed 316L steels are described. GSed surface layer improves damage defusing ability, thus enhanced fatigue property. Abstract: Low-cycle fatigue behavior of gradient structured (GSed) 316L steels is investigated. The results show that both the homogeneous and gradient structures exhibit first cyclic hardening then cyclic softening. The GSed surface layer can, however, speed up cyclic hardening and extend cyclic softening processes. The analyses using hysteresis energy-based criterion indicates that the former phenomenon can be attributed to the reduced fatigue damage capacity, while the latter to the improved ability of damage defusing. This finding accordingly pinpoints that the retarded fatigue damage accumulation process has been acting as the main contributor to the enhanced fatigue performance of GSed 316L steels.